Rethinking Financial Inclusion in the Digital Age: Determinants of Fintech Adoption in Indonesian Households - Axellina Muara Setyanti; M. Afif Khoiruddin; Firdaus Finuliyah (Neo Journal of economy and social humanities, 2025)
This study examines the determinants of fintech adoption among Indonesian households using nationally representative microdata from SUSENAS 2022 and binary logistic regression analysis. The findings reveal that fintech adoption remains limited, with only 5.48% of households reporting the use of digital financial services such as mobile banking. Among the determinants, savings ownership emerges as the strongest predictor, associated with a 12% higher probability of adopting fintech, underscoring the importance of prior financial engagement. Other significant factors include educational attainment, ICT experience, and formal employment. The analysis also highlights notable geographic variation. Education increases the probability of fintech use by 1.37% in urban areas but only 0.27% in rural areas. Similarly, ICT experience is associated with a 4.72% increase in adoption probability in urban areas, compared to 1.28% in rural settings, reflecting unequal returns to human capital across region. Formal employment and land ownership play a more influential role in rural areas. In contrast, participation in government assistance programs such as PKH and BPNT is negatively associated with fintech use across both settings, indicating that digital transfers alone are insufficient to foster sustained financial inclusion. These results highlight the urgency of designing context-sensitive fintech policies that address digital literacy, institutional trust, and inclusive program integration.